Factors influencing Islamic banking selection criteria among muslim international students of selected universities in northern states of Malaysia - Abdi, Mohamed Hassan (2015)
The number of Muslim international students studying in the Malaysian institution of Higher education is incessantly growing. The extensive numbers of Muslim international students in Malaysia have contributed not only the country’s education sector, but even the Islamic banking industry as well. Thus, the aim of the study is to examine the factors that influence Muslim international student’s selection criteria of the Islamic banking sector. This study focuses on all international students in Northern State of Malaysia, especially three public universities, namely University Utara Malaysia, University Sains Malaysia, and University Malaysia Perlis. A total of 217 questionnaires are distributed and 163 usable responses were analyzed. The outcome of the study indicates that 43 percent of the variance of Muslim international student’s selection criteria to choose Islamic banking system can be explained by the variables which are religiosity, knowledge, service, reputation. Furthermore out of the four independent variables, the variables, specifically knowledge, service and reputation are found significant to the selection criteria of Islamic banking